Um modelo de audiogame móvel acessível e customizável para práticas ortográficas com o Braille - Araújo, Maria da Conceição Carneiro (2016)
Serious games for mobile platforms have great potential to promote the learning processes. It’s still a challenge to establish appropriate approaches to model, build, and turn accessible the interfaces of these games. In this context, our research proposes a model for mobile audiogames, which are accessible and customizable, and have as target the domain of orthographic practices with Braille by people with visual disabilities. The model proposes an architecture for the development of such audiogames as well as guidelines to improve the accessibility and usability of game interfaces. As a proof of concept, a mobile audiogame was developed. The game is accessible to people who are blind, called Ortomonstro. This audiogame comprises a mobile Android application and a customization Web interface. Its goal is to be more than a mobile audiogame, since Ortomonstro follows the design principles of Customizable Learning Objects (CLO). The Web interface provides the generation of configurations and customizations of questions, answers, and media content of the game (e.g., images, audio files). We have implemented usability and accessibility evaluation in two phases. First, it was applied with four special education teachers, and, then, with twelve visually impaired users. All teachers reported satisfaction on the use of both the Web interface and the mobile game. The positive evaluation of users exceeded the 80 % in assessment of skills, acceptance, and entertainment.